Soil microorganisms and methane emissions in response to short-term warming field incubation in Svalbard - Li, Jiakang; Zhu, Zhuo-Yi; Yang, Zhifeng; Li, Weiyi; Lv, Yongxin; Zhang, Yu (Frontiers in Microbiology, 2023)
Introduction: Global warming is caused by greenhouse gases (GHG). It has been found that methane (CH4) release from Arctic permafrost, soil, ocean, and sediment is closely related to microbial composition and soil factors caused by warming based on long-term observations during several months or years. However, with the development of global warming, how long continuous warming affects the microbial composition and GHG release from soils along Arctic glacial meltwater rivers is unclear. Methods: In this study, the soil upstream of the glacial meltwater river (GR) and the estuary (GR-0) in Svalbard, with strong soil heterogeneity, were subjected to short-term measured by days field incubation at 2°C (in situ temperature), 10°C and 20°C with anoxic conditions, respectively. Bacterial composition and CH4 production potential were determined based on high-throughput sequencing and physiochemical properties measurement. Results: Our results revealed bacterial 16S rRNA gene copy number, bacterial composition, and methanogenic potential (mcrA gene copy number and CH4 concentration) were not different during warming field incubation for 7 and 13 days with incubation temperatures increasing, respectively. The CH4 concentration at the GR site was higher than that at the GR-0 site, but the mcrA gene was lower than that at the GR-0 site. Discussion: Based on the warming field incubation, our results indicate that short-term warming measured in days affects soil microbial composition and CH4 concentration less than the spatial scale, highlighting the importance of warming time in influencing CH4 release from soil. In summary, our research implied that microbial composition and CH4 emissions in soil warming have no increase in the first several days, but the particular site is more important. Yet, emissions will gradually increase first and then decrease with the warming time increasing for the long term. These results are important for understanding and exploring the GHG emission fluxes of high-latitude ecosystems under global warming.